INTERNATIONAL LAW AS POLITICAL INSTRUMENT: SEVERAL OF INDONESIA’S EXPERIENCES AS A CASE STUDY - Juwana, Hikmahanto (Indonesian Journal of International Law, 2021)
International law in its basic concept is intended to serve as legal framework for society of States. International law prescribes what is right and what is wrong; it also prescribes how State behaves toward one another; and it provides sanctions. However, the above description is international law is frequently used as a political instrument by States. It can be an instrument to exert pressure, instrument for intervening on other States domestic affairs without considered as violation and it can also be used to justify States’ actions. The present article and how Indonesia has used international law to further its national policy.